2021
DOI: 10.31234/osf.io/8zwc4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Trump a Symptom or a Cause? Economic, Political and Ideological Foundations of the COVID-19 Outbreak in the United States (First Draft)

Abstract: The US is amongst the worst-performing countries at combating COVID-19. And within the US, red (Republican) states have significantly higher cases per capita than blue (Democratic) states. We use cross-country, state, and county-level data to provide a comprehensive analysis of economic, political, and psychological factors contributing to these differences. An inferior social safety net and American conservatism systematically correlate with the realization and effectiveness of non-pharmaceutical intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…As we noted above, the contrast between responses on mask-wearing and SIP policies is predictable on the basis of arguments made in Cui et al [16]. There we argue that SIP has a real economic cost for anyone who cannot work from home, as noted in Thunstrom et al [15].…”
Section: Shelter-in-place Orderssupporting
confidence: 49%
See 3 more Smart Citations
“…As we noted above, the contrast between responses on mask-wearing and SIP policies is predictable on the basis of arguments made in Cui et al [16]. There we argue that SIP has a real economic cost for anyone who cannot work from home, as noted in Thunstrom et al [15].…”
Section: Shelter-in-place Orderssupporting
confidence: 49%
“…This suggests that the factors that influence choices about enacting policies are different in the two cases, with economic factors weighing more heavily in SIP choices and political/symbolic factors more important in mask-related policies. The evidence in Cui et al [16] clearly supports this.…”
Section: Empirical Testingmentioning
confidence: 77%
See 2 more Smart Citations
“…Although a similar mask study was carried out in Wisconsin, United States (Haischer et al, 2020), it was conducted in a situation where infection risks were extremely high (US total at the time of study: 7 million confirmed cases and over 200,000 deaths nationwide). It was also carried out where mask policies were not clear, and in some instances, people refused to adhere to health guidelines for political or personal reasons (Cui et al, 2021). Another cross-national study found collectivistic cultures were more likely to wear masks than individualistic cultures (Lu et al, 2021).…”
Section: Individual and Cultural Factorsmentioning
confidence: 99%